Komunikasi Efektif Untuk Meningkatkan Kualitas SDM, Pemasaran, dan Performa Keuangan Desa Wisata Kelor Yogyakarta - Susi Astuti; Rizki Ramadhani (LP3M Universitas Putra Bangsa, 2024)
Effective communication plays a crucial role in improving the financial performance of an organization. With good communication between management, employees, and other stakeholders, information regarding financial goals, strategies, and business developments can be conveyed clearly and timely. This enables better decision-making, more efficient risk management, and more productive collaboration. Thus, effective communication creates a transparent work environment capable of enhancing the overall financial performance of the organization. The Community Service Activities in Kelor Village, Turi Sleman, Yogyakarta aims to enhance the financial performance of the tourism village through effectively communicated strategies across all organizational elements